Pelayanan Konseling Terhadap Pencandu Narkoba Sebagai Peran Nyata Kekristenan - Abednego; Wahyuni, Sri (Kaluteros Jurnal Teologi Dan Pendidikan Agama Kristen, 2025)
Drugs basically have good uses in the medical world, but they have been misused so that drugs are considered bad goods. Drugs in the world of medicine are studied as medicines that are used according to the dosage contained therein. If used inappropriately it will result in addiction. Drug addicts are not enemies but friends who must be helped to escape the shackles of these drugs. This research uses a descriptive analysis method with a qualitative approach, with the steps: collection, classification and analysis, making conclusions and reports with the main aim of creating an objective depiction of a situation in a description. The results of this research are that drug addicts are very important friends served by Christian counseling services as an effort to heal drug addicts, not only servants of God who are involved, lay people can also be involved in counseling services for drug addicts. The author believes that firstly "Drugs do not destroy but are misused so that they are destructive" secondly "Drug addicts are not enemies but friends who must be helped".